2000
DOI: 10.1590/s1415-43662000000300008
|View full text |Cite
|
Sign up to set email alerts
|

Potential evapotranspiration estimates for northeast Brazil using GOES-8 data

Abstract: In this study, an empirical method proposed by Caselles et al. (1992a) is utilized to determine the potential evapotranspiration (ETP) on a regional scale. This method uses the global solar radiation data retrieved by the global radiation model GL1.0, which in turn utilizes data from the visible channel of the GOES-8 satellite. This method is applied to the northeast region of Brazil, using daily and monthly climatological data as the ground truth information to estimate the ETP and the estimated daily ETP dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Due to regional characteristics, ET rate is distinct in large areas, that is, the seashore coast of the northern Brazil and the inner regions have a higher temperature than along the eastern coast. Furthermore, the east coast is more affected by meteorological systems, such as the sea breeze, easterly waves and cold fronts that comes from the south region of the country; while the atmospheric circulation over the Northeastern region is mainly drawn by the orographyc effects 13 . In the middle-east, the annual cycle of the ET is well defined, with maximum values occurring during January and May and the minimum one in September (dry period) varying between 1-2 mm/day in the north of Minas Gerais State.…”
Section: Resultsmentioning
confidence: 99%
“…Due to regional characteristics, ET rate is distinct in large areas, that is, the seashore coast of the northern Brazil and the inner regions have a higher temperature than along the eastern coast. Furthermore, the east coast is more affected by meteorological systems, such as the sea breeze, easterly waves and cold fronts that comes from the south region of the country; while the atmospheric circulation over the Northeastern region is mainly drawn by the orographyc effects 13 . In the middle-east, the annual cycle of the ET is well defined, with maximum values occurring during January and May and the minimum one in September (dry period) varying between 1-2 mm/day in the north of Minas Gerais State.…”
Section: Resultsmentioning
confidence: 99%
“…The authors reported daily mean errors generally within ±10 W m −2 with standard deviations lower than 20 W m −2 . The GL1.2 database has contributed to the validation of numerical weather prediction models and data assimilation systems [29,30], to climatological and environmental studies [31][32][33], to hydrological modeling [34], to potential evapotranspiration estimation [35] and, last but not least, to solar resource assessment [36].…”
Section: Introductionmentioning
confidence: 99%